A guaB mutant strain of Rhizobium tropici CIAT899 pleiotropically defective in thermal tolerance and symbiosis - Riccillo, Pablo Miguel (2000)
Rhizobium tropici strain CIAT899 displays a high intrinsic thermal tolerance, and had been used in this work to study the molecular basis of bacterial responses to high temperature. We generated a collection of R. tropici CIAT899 mutants affected in thermal tolerance using Tn5-luxAB mutagenesis and described the characterization of a mutant strain, CIAT899-10T, that fails to grow under conditions of high temperature. Strain CIAT899-10T carries a single transposon insertion in a gene showing a high degree of similarity with the guaB gene of Escherichia coli and other organisms, encoding the enzyme inosine monophosphate dehydrogenase. The guaB strain CIAT899-10T does not require guanine for growth due to an alternative pathway via xanthine dehydrogenase and, phenotypically, in addition to the thermal sensitivity, the mutant is also defective in symbiosis with beans, forming nodules that lack rhizobial content. Guanine and its precursors restore wild-type tolerance to grow at high temperature. Our data show that, in R. tropici, the production of guanine via inosine monophosphate dehydrogenase is essential for growth at extreme temperatures and for effective nodulation.